Identification of trends, direction of distribution and spatial pattern of tuberculosis disease (2015-2017) in Penang - Nur Afiqah Ariffin,; Wan Mohd Muhiyuddin Wan Ibrahim,; Ruslan Rainis,; Narimah Samat,; Mohammad Izzamil Mohd Nasir,; Siti Masayu Rosliah Abdul Rashid,; Azizul Ahmad,; Yaniza Shaira Zakaria, (Penerbit Universiti Kebangsaan Malaysia, 2024)
In Malaysia, the annual tuberculosis (TB) cases exhibit a consistent upward trend, and Penang has experienced a similar increase since 2011. This research aims to analyze the trend, distribution direction, and spatial patterns of TB in Penang from 2015 to 2017, utilizing data from 4,015 TB cases obtained from the TB/Leprosy Unit of the Penang State Department. The study employs three analytical techniques: descriptive analysis, global Moran's I, and central feature with standard deviation ellipse, which measures the trend by calculating standard distances in the X and Y directions to identify the focus and movement of tuberculosis cases. The findings indicate a higher incidence of tuberculosis in males compared to females, with the age group of 45 to 64 years having the highest number of TB patients in Penang. The aging process contributes to weakened immune systems, facilitating tuberculosis development in this age group. The spatial pattern trends for the three study years (2015 to 2017) are scattered, as revealed by the Moran index, indicating a non-dynamic and clustered pattern of TB cases in Penang.The main center of TB case distribution is identified in the George Town subdistrict, situated in the Northeast district, particularly concentrated in urban areas. Rural areas exhibit lower TB cases. The standard deviation ellipse in the north to east direction suggests a potential risk of TB spread, especially to nearby neighborhoods, in the upcoming years.